Novel White Matter Tract Integrity Metrics Sensitive to Alzheimer Disease Progression - Fieremans, E.; Benitez, A.; Jensen, J.H.; Falangola, M.F.; Tabesh, A.; Deardorff, R.L.; Spampinato, M.V.S.; Babb, J.S.; Novikov, D.S.; Ferris, S.H.; Helpern, J.A. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: Along with cortical abnormalities, white matter microstructural changes such as axonal loss and myelin breakdown are implicated in the pathogenesis of Alzheimer disease. Recently, a white matter model was introduced that relates non-Gaussian diffusional kurtosis imaging metrics to characteristics of white matter tract integrity, including the axonal water fraction, the intra-axonal diffusivity, and the extra-axonal axial and radial diffusivities. MATERIALS AND METHODS: This study reports these white matter tract integrity metrics in subjects with amnestic mild cognitive impairment (n = 12), Alzheimer disease (n = 14), and age-matched healthy controls (n = 15) in an effort to investigate their sensitivity, diagnostic accuracy, and associations with white matter changes through the course of Alzheimer disease. RESULTS: With tract-based spatial statistics and region-of-interest analyses, increased diffusivity in the extra-axonal space (extra-axonal axial and radial diffusivities) in several white matter tracts sensitively and accurately discriminated healthy controls from those with amnestic mild cognitive impairment (area under the receiver operating characteristic curve = 0.82–0.95), while widespread decreased axonal water fraction discriminated amnestic mild cognitive impairment from Alzheimer disease (area under the receiver operating characteristic curve = 0.84). Additionally, these white matter tract integrity metrics in the body of the corpus callosum were strongly correlated with processing speed in amnestic mild cognitive impairment (r = |0.80–0.82|, P < .001). CONCLUSIONS: These findings have implications for the course and spatial progression of white matter degeneration in Alzheimer disease, suggest the mechanisms by which these changes occur, and demonstrate the viability of these white matter tract integrity metrics as potential neuroimaging biomarkers of the earliest stages of Alzheimer disease and disease progression. ADAlzheimer diseaseaMCIamnestic mild cognitive impairmentAWFaxonal water fractionCPScomposite processing speedDKIdiffusional kurtosis imagingFAfractional anisotropyNChealthy controlsTBSStract-based spatial statisticsWMTIwhite matter tract integrity